Gold and hypervalent iodine(iii): liaisons over a decade for electrophilic functional group transfer reactions. Issue 18 (24th February 2020) - Banerjee, Somsuvra; Bhoyare, Vivek W.; Patil, Nitin T.
Abstract : Building on mechanistic perspective, the review intends to demonstrate how the uniqueness of Au-catalysts has realized a myriad of electrophilic functional group transfer reactions with the use of hypervalent iodine(iii ) reagents over the last decade. Abstract : Over the last two decades, hypervalent iodine(iii ) reagents have evolved from being 'bonding curiosities' to mainstream reagents in organic synthesis, in particular, electrophilic functional group transfer reactions. In this context, gold catalysts have not only emerged as a unique toolbox to facilitate such reactions (especially alkynylations) but also opened new possibilities with their different modes of reactivities for other functional group transfer reactions (acetoxylations and arylations). This feature article critically summarizes hitherto all such Au-catalyzed electrophilic functional group transfer reactions with hypervalent iodine(iii ) reagents, emphasizing their mechanistic aspects.